The legal feasibility of adopting a sugar-sweetened beverage tax in seven sub-Saharan African countries - Safura Abdool Karim; Agnes Erzse; Anne-Marie Thow; Hans Justus Amukugo; Charles Ruhara; Gemma Ahaibwe; Gershim Asiki; Mulenga M. Mukanu; Twalib Ngoma; Milka Wanjohi; Abel Karera; Karen Hofman (Taylor & Francis Group, 2021)
Background: A number of countries have adopted sugar-sweetened beverage taxes to prevent non-communicable diseases but there is variance in the structures and rates of the taxes. As interventions, sugar-sweetened beverage taxes could be cost-effective but must be compliant with existing legal and taxation systems. Objectives: To assess the legal feasibility of introducing or strengthening taxation laws related to sugar-sweetened beverages, for prevention of non-communicable diseases in seven countries: Botswana, Kenya, Namibia, Rwanda, Tanzania, Uganda and Zambia. Methods: We assessed the legal feasibility of adopting four types of sugar-sweetened beverage tax formulations in each of the seven countries, using the novel FELIP framework. We conducted a desk-based review of the legal system related to sugar-sweetened beverage taxation and assessed the barriers to, and facilitators and legal feasibility of, introducing each of the selected formulations by considering the existing laws, laws related to impacted sectors, legal infrastructure, and processes involved in adopting laws. Results: Six countries had legal mandates to prevent non-communicable diseases and protect the health of citizens. As of 2019, all countries had excise tax legislation. Five countries levied excise taxes on all soft drinks, but most did not exclusively target sugar-sweetened beverages, and taxation rates were well below the World Health Organization's recommended 20%. In Uganda and Kenya, agricultural or HIV-related levies offered alternative mechanisms to disincentivise consumption of sugar-sweetened beverages without the introduction of new taxes. Nutrition-labelling laws in all countries made it feasible to adopt taxes linked to the sugar content of beverages, but there were lacunas in existing infrastructure for more sophisticated taxation structures. Conclusion: Sugar-sweetened beverage taxes are legally feasible in all seven countries Existing laws provide a means to implement taxes as a public health intervention.